Surgical Treatment of Vertex Epidural Hematoma (VEDH): Experience of One-piece Central Craniotomy for Evacuation Compared to the Relevant Literature - Eljili, Fawaz; Zidan, Ahmed; Mustafa, Mohamed; Ali, Honida (Medical Science: Trends and Innovations Vol. 2, 2025)
Introduction: Vertex EDH is a rare type of EDH found in the highest skull vault and accounts for 0.024% of all head injuries and 0.47-8.20% of all intracranial extradural hematomas. Some cases of VEDHs extended beyond the anatomical area of the vertex. It is commonly caused by linear crossing skull fracture over the sinus caused by direct insult to the vertex or diastasis of the sagittal suture. VEDH presentation is usually atypical with non-specific symptoms and signs and can be presented as acute, subacute, or chronic. VEDH radiological feature and diagnosis is considered challenging, which is explained by its higher location in the skull vault. Ct brain with the coronal cut is the best or sometimes MRI may be requested. Aim: The aim of the study is to evaluate the surgical management of vertex epidural hematoma (VEDH). This study added a case study approach and experience through one-piece craniotomy without leaving the central bone strip. It was a comparison between each regarding the advantages and disadvantages. Methods: A review was done through the engine search PubMed and Google Scholar, using the keywords and terms (vertex), (epidural) or (extradural hematoma) presentation, the management or surgical technique, case report, case series or other relevant reviews are revised for the relevant information for our title without specification to a period. A study was conducted at the Department of Neurosurgery for neurotrauma cases at Al tamyouz (haj al mardi recently) accident and trauma hospital. Five cases out of 115 cases of EDH (4.34%) were diagnosed as VEDH during June 2019-June 2020. All five cases were operated through central vertex craniotomy with one bone flap including the bone over the sinus, unlike the way mentioned in the literature by doing biparietal separate para-sagittal craniotomy with a central bone strip left in place over the sinus. Results: Discomfort during the evacuation and difficulty in conducting direct sinus repair in case of significant tear when using the mentioned approach in the literature. In addition to that the risk of injury of the important draining veins during dural tack up. From the case study, it is stated that the advantages of such a craniotomy include direct exposure of the entire hematoma, considering that the sinus is already pushed downward by the hematoma, creating a tamponade effect on the sinus. This reduces the risk of early sinus bleeding. Conclusion: Vertex EDH is a rare type of EDH but challenging in both diagnosis and surgical treatment. In the literature, the commonly used approach for surgery was biparietal parasagittal craniotomy. This study encourages the utilization of one-piece craniotomy without leaving the central bone strip approach of craniotomy and reports any advantages or disadvantages that may have been encountered in the literature.